LARANGAN PERKAWINAN SEPERSUSUAN DITINJAU DARI PERSPEKTIF HUKUM ISLAM DAN MEDIS - Fahrul Fauzi (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTIslam considers that marriage is not a relationship like an ordinary civil contract but a very strong contract or a solid agreement (mitsaaqaan ghaliizhaan). Marriage must pay attention to harmony, conditions, and restrictions so that it can be said to be legal according to the law. One limitation that needs to be considered is the prohibition of the marriage of susuan relations (one breastfeed). The prohibition of the marriage of susuan relations stipulated by Allah in the Qur'an verse must have scientific reasons. This article discusses the prohibition of the marriages of susuan relations in terms of Islamic law and medical aspects. Review of Islamic Law to find out how the limits so that someone can be said as a susuan relations. While a medical review is needed to uncover the scientific reasons why the prohibition of the marriage of susuan relations is prohibited by Allah. In this study, the author uses a normative juridical approach by analyzing secondary data, this research can also be said as a library research. This research approach is supported by using descriptive qualitative analysis methods. Keywords: Marriage Prohibition, Susuan Relations, Islamic Law, Medical